Dry Sliding Wear Behavior of Cemented Carbide at Elevated Temperatures - Zamri, Wan Fathul Hakim W; Shamsudeen, Azhari; Din, Muhamad Faiz Md (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
The material for a cutting tool needs to be carefully selected to withstand high temperatures during cutting and have good wear performance. The use of cutting tools made from cemented carbide material was studied due to its potential in terms of mechanical properties that are ideal at high temperatures up to 1000 °C and being cheaper than other materials. This investigation of the dry wear of this cutting material focused on temperatures of 25 °C, 200 °C, and 300 °C, with loads of 50 N, 100 N, and 150 N. The weight loss, friction coefficient, and change of the pin microstructure were determined. It was found that the higher the temperature and load applied to the cemented carbide pin, the more the microstructure changed, and the percentage of weight loss increased up to 0.55%. The wear rate on the cemented carbide pins was higher when applied to a stainless steel disc compared to a mild steel disc. The simulation revealed that the von Mises stress on the stainless steel disc was 51.759 Pa, while that on the mild-steel disc was 60.379 Pa. This indicates that both materials did not fail because the von Mises stress was lower than the disc yield stress.